Coping with strategic ambiguity in planning sustainable road development: balancing economic and environmental interests in two highway projects in Indonesia. Issue 3 (3rd May 2020) - Suprayoga, Gede B.; Witte, Patrick; Spit, Tejo
ABSTRACT: In planning regional road development, planners often face a challenge to reconcile various interests and interpretations on the ultimate goals which complicate the discussion decision-making processes. This situation is defined as strategic ambiguity. Standard procedures for impact assessment are mostly ineffective at offering solutions that satisfy all involved stakeholders. This paper analyses the situation by using a Multiple Stream Framework (MSF) approach. MSF identifies three factors, labelled "streams', i.e. the problems, the solutions, and the politics streams, that open sustainability 'windows' for integrating different interests. This paper investigates the opening of such windows in two highway projects in Indonesia. Both projects showed a high ambition for achieving environmental sustainability. In these cases, the window was opened through (i) recognition of the problems and the solutions by the active involvement of stakeholders, (ii) coalitions with influential stakeholders for political supports, and (iii) mobilization of resources and policy networks by the stakeholders. It is concluded that planners might influence the streams to outline decision-making processes and to implement environmental impact assessments effectively.